2011
DOI: 10.5406/amerjpsyc.124.3.0313
|View full text |Cite
|
Sign up to set email alerts
|

The Odd–Even Effect in Sudoku Puzzles: Effects of Working Memory, Aging, and Experience

Abstract: The odd–even effect in numerical processing has been explained as the easier processing of even numbers compared with odd numbers. We investigated this effect in Sudoku puzzles, a reasoning problem that uses numbers but does not require arithmetic operations. Specifically, we asked whether the odd–even effect occurred with Sudoku puzzles and whether individual differences in working memory (WM), aging, and experience with Sudoku modulated this effect. We manipulated the presence of odd and even numbers in Sudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…However, the frequency association was less linear.The analysis identified benefit across several cognitive domains including episodic memory, spatial working memory, attention, processing speed, and executive function. This correlates with previous studies, which have also indicated associations with working memory, problem solving, and attention [7][8][9][10]. Combined, the literature appears to suggest a global cognitive impact, which is not restricted to a specific cognitive domain.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…However, the frequency association was less linear.The analysis identified benefit across several cognitive domains including episodic memory, spatial working memory, attention, processing speed, and executive function. This correlates with previous studies, which have also indicated associations with working memory, problem solving, and attention [7][8][9][10]. Combined, the literature appears to suggest a global cognitive impact, which is not restricted to a specific cognitive domain.…”
supporting
confidence: 90%
“…005, d = 0.07 and 0.09). This correlates with previous studies, which have also indicated associations with working memory, problem solving, and attention [7][8][9][10]. Analysis of data from the four PCTB measures showed consistent superior performance, with effect sizes ranging from d = 0.17 to d = 0.47.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Few studies have examined the cognitive demands associated with completing Sudoku puzzles or its potential protective factor as a cognitively stimulating activity for delaying cognitive decline. A comparable study did, however, report an association between accuracy on Sudoku puzzles and working memory, as measured by the Wisconsin Card Sorting Test and Backwards Digit Span Task (Chang and Gibson, ). Authors of a further study suggest that deactivation in the posterior cingulate cortex and precuneus found during Sudoku completion is likely due to reallocation of cognitive resources required during the task including for working memory, preparatory attention, target detection and monitoring of response accuracy (Jin et al ., ).…”
Section: Discussionmentioning
confidence: 98%